2007
DOI: 10.1029/2006gl028462
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a shoaling internal solitary wavetrain

Abstract: Field observations of an internal solitary wavetrain impacting a shoaling bottom are presented. Measurements of the spatio‐temporal characteristics of the shoaling waves are given, as well as estimations of the mixing they may have caused upon impact. The observations are discussed in the context of numerical simulations, laboratory experiments, and hypotheses recently raised on the origin and evolution of internal solitary waves in coastal environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 13 publications
2
57
1
Order By: Relevance
“…For example, observations in the Strait of Juan de Fuca suggested that cross-isobath Ekman transport associated with alongchannel tidal currents was essential to generate large vertical isopycnal excursions (Martin et al 2005). Crossisobath propagation of ISWs was also observed in the St. Lawrence Estuary (Bourgault et al 2007) and in the Faeroe-Shetland Channel (Hosegood and van Haren 2004). It is quite possible that these waves were generated by the interaction between the lateral currents and lateral bathymetry change.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, observations in the Strait of Juan de Fuca suggested that cross-isobath Ekman transport associated with alongchannel tidal currents was essential to generate large vertical isopycnal excursions (Martin et al 2005). Crossisobath propagation of ISWs was also observed in the St. Lawrence Estuary (Bourgault et al 2007) and in the Faeroe-Shetland Channel (Hosegood and van Haren 2004). It is quite possible that these waves were generated by the interaction between the lateral currents and lateral bathymetry change.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This basic scenario has been observed in several places in the ocean, For instance, this phenomena has been reported by Salusti et al (1989) in the Eastern Mediterranean, by Holloway et al (1997Holloway et al ( , 1999 and in the North West Shelf of Australia, by Hsu et al (2000) in the East China Sea, during the ASIAEX experiment in the South China Sea by Duda et al (2004), Liu et al (1998Liu et al ( , 2004, Orr and Mignerey (2003), , Yang et al (2004), Zhao et al (2003Zhao et al ( , 2004 and Zheng et al (2003), and on the New Jersey shelf by Shroyer et al (2009). Further, numerical simulations of the full Euler equations predict polarity reversal in Lake Constance (Vlasenko and Hutter, 2002), in the Andaman Sea (Vlasenko and Staschuk, 2007) and in the Saint Lawrence estuary (Bourgault et al, 2007). But elsewhere in the ocean, where there are no such critical points, the shoreward propagating small-amplitude internal solitary waves are expected to deform adiabatically (at least within the framework of the vKdV equation).…”
Section: Application To Internal Solitary Waves In the South China Seamentioning
confidence: 97%
“…Correspondence to: R. Grimshaw (r.h.j.grimshaw@lboro.ac.uk) for the transformation of a nonlinear wave in the shelf zone due to changes in the depth and the background density stratification, including soliton fission (Zheng et al, 2001;Zhao et al, 2003;Orr and Mignerey, 2003;Helfrich, 1992;Vlasenko et al, 2005;Bourgault et al, 2007). Theoretically such processes have been well studied for a smoothly and slowly varying background when the Korteweg-de Vries equation and its modifications can be applied (Djordevic and Redekopp, 1978, Helfrich and Melville, 1986, Holloway et al, 1997Zheng et al, 2001;Grimshaw et al, 2004Grimshaw et al, , 2007.…”
Section: Observations Show That There Is a Wide Variety Of Processesmentioning
confidence: 99%